Allelic variation in the indoleacetic acid-lysine synthase gene of the bacterial pathogen Pseudomonas savastanoi and its role in auxin production - Pintado Calvillo, Adrián; Domínguez Cerván, Hilario; Pastor, Victoria; Vincent, Marissa; Goo Lee, Soon; Flors, Víctor; Ramos-Rodríguez, Cayo Juan (Frontiers Media, 2023)
Indole-3-acetic acid (IAA) production is a pathogenicity/virulence factor in the Pseudomonas syringae complex, including Pseudomonas savastanoi. P. savastanoi pathovars (pvs.) genomes contain the iaaL gene, encoding an enzyme that catalyzes the biosynthesis of the less biologically active compound 3-indole-acetyl-ϵ-L–lysine (IAA–Lys). Previous studies have reported the identification of IAA–Lys in culture filtrates of P. savastanoi strains isolated from oleander (pv. nerii), but the conversion of IAA into a conjugate was not detectable in olive strains (pv. savastanoi). In this paper, we show the distribution of iaaL alleles in all available P. savastanoi genomes of strains isolated from woody hosts. Most strains encode two different paralogs, except for those isolated from broom (pv. retacarpa), which contain a single allele. In addition to the three previously reported iaaL alleles (iaaLPsv, iaaLPsn and iaaLPto), we identified iaaLPsf, an exclusive allele of strains isolated from ash (pv. fraxini). We also found that the production of IAA–Lys in P. savastanoi pv. savastanoi and pv. nerii depends on a functional iaaLPsn allele, whereas in pv. fraxini depends on iaaLPsf. The production of IAA–Lys was detected in cultures of an olive strain heterologously expressing IaaLPsn-1, IaaLPsf-1 and IaaLPsf-3, but not when expressing IaaLPsv-1. In addition, Arabidopsis seedlings treated with the strains overproducing the conjugate, and thus reducing the free IAA content, alleviated the root elongation inhibitory effect of IAA. IAA–Lys synthase activity assays with purified allozymes confirmed the functionality and specificity of lysine as a substrate of IaaLPsn-1 and IaaLPsf-3, with IaaLPsf-3 showing the highest catalytic efficiency for both substrates. The IAA–Lys synthase activity of IaaLPsn-1 was abolished by the insertion of two additional tyrosine residues encoded in the inactive allozyme IaaLPsv-1.

These results highlight the relevance of allelic variation in a phytohormone-related gene for the modulation of auxin production in a bacterial phytopathogen.
AP and HD-C were supported by the FPU14/05551 and PRE2021-099113 predoctoral grants, respectively. CR was supported by the AGL2017-82492-C2-1-R and PID2020- 115177RB-C21 project grants from the Spanish Ministry of Science, Innovation and Universities (Spain), co-financed by the European Regional Development Fund (ERDF). VP and VF were supported by the GV/2018/115 and CIACO/2021/092 grant projects from Generalitat Valenciana and the RTI2018-094350-BC33 grant from the Spanish Ministry of Science, Innovation and Universities. MV and SL were supported by project grant A20-0079 from The North Carolina Biotechnology Center (NCBC).
Keywords: Pseudomonas syringae - Genética; IAA; Indole-3-acetic acid; IAA-lysine synthase; Pseudomonas syringae; Pseudomonas savastanoi; Allelic variation; Auxin